Pengaruh Gaji Dan Budaya Organisasi Terhadap Kinerja Guru SD Swasta Di Kecamatan Rambutan Kota Tebing Tinggi - Jayanti, Suci Etri; Damanik, Ayu Zurlaini; Matondang, Andrina Amalia (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
Based on existing phenomena from the research object carried out by researchers, there is a decline in the performance of private elementary school teachers in Rambutan District, Tebing Tinggi City due to low salaries and organizational culture which is still carried out by some teachers, namely being reluctant to get involved in school activities which ultimately has an impact on teacher performance, resulting in a less harmonious relationship between teachers. The aim of this research is to determine the influence of salary and organizational culture on the performance of private elementary school teachers in Rambutan District, Tebing Tinggi City. The method used in this research is Multiple Linear Regression with the IBM SPSS 25.00 application. The results of this research show that the salary and organizational culture variables influence the performance of private elementary school teachers in Rambutan District, Tebing Tinggi City, and the salary and organizational culture variables simultaneously influence the performance of private elementary school teachers in Rambutan District, Tebing Tinggi City.